2001
DOI: 10.3168/jds.s0022-0302(01)74690-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Time of Insemination on Number of Accessory Sperm, Fertilization Rate, and Embryo Quality in Nonlactating Dairy Cattle

Abstract: Two experiments were conducted to determine the effect of insemination time on number of accessory sperm per embryo (ovum), fertilization rate, and embryo quality. Semen was collected from three fertile Holstein bulls and cryopreserved in egg yolk-citrate-glycerol. In experiment 1, cows were continuously monitored for behavioral estrus by the HeatWatch estrous detection system and were artificially inseminated (AI) with one 0.5-ml straw (25 x 10(6) sperm) at the onset of estrus (AI 0 h), 12 h after onset (AI 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
80
1
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 22 publications
9
80
1
5
Order By: Relevance
“…These findings were in agreement with those of Saacke et al (2000) and Dalton et al (2001). On a molecular level, sperm surface proteins are thought to participate in zona binding and fertilization (Talbot et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…These findings were in agreement with those of Saacke et al (2000) and Dalton et al (2001). On a molecular level, sperm surface proteins are thought to participate in zona binding and fertilization (Talbot et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the average milk yield per cow per lactation in Nakashunbetsu rose from 7,700 kg in 1992 to 8,100 kg in 2000. These changes might cause poor expression of estrous behavior and shortening of the duration of estrus [7][8][9][10][11][12]. As the consequence, the estrous detection has become more difficult than ever [13].…”
mentioning
confidence: 99%
“…Previous reports have revealed that the distribution of accessory sperm cells is very skewed, with a median of 1 to 10 per ovum/ embryo [10,11] and a mode of 0 per ovum/embryo [10]. In contrast, more than 50 accessory sperm cells per ovum/embryo were observed with low frequency, and good to excellent embryos, which are generally used for genetic diagnosis, had a higher accessory sperm number than degenerate or fair to poor embryos [10].…”
Section: Resultsmentioning
confidence: 91%
“…Saacke [10] reported that the average, median and mode accessory sperm cell numbers in the zonae pellucidae of ova and embryos were 12.0, 2.4 and 0, respectively. Dalton et al [11] also reported that the range of the accessory sperm cell number per embryo was 0 to 216. The DNA of most vertebrate sperm cells is packaged by protamines, and disulfide bonds between DNA-bound protamines help stabilize the chromatin of mature sperm cells [12].…”
mentioning
confidence: 98%